2017
DOI: 10.1186/s40814-017-0191-2
|View full text |Cite
|
Sign up to set email alerts
|

The ReSiT study (reducing sitting time): rationale and protocol for an exploratory pilot study of an intervention to reduce sitting time among office workers

Abstract: BackgroundDesk-based workers engage in long periods of uninterrupted sitting time, which has been associated with morbidity and premature mortality. Previous workplace intervention trials have demonstrated the potential of providing sit-stand workstations, and of administering motivational behaviour change techniques, for reducing sitting time. Yet, few studies have combined these approaches or explored the acceptability of discrete sitting-reduction behaviour change strategies. This paper describes the ration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…There is evidence that suggests the long-term indirect costs of employees’ presenteeism and absenteeism stemming from sedentary behaviour-associated illness might be higher than the cost of height-adjustable desks. For instance, height-adjustable desks cost ≥ £279 (US $375) per unit for a single display [61] and ≥ £305 (US $400) per unit for a dual display [62], which compares favourably with the indirect cost of presenteeism for businesses (which is far more than the cost of absenteeism) that was approximately £194 (US $255) per employee per annum [63]. Previous work has shown that organisational managers and employers are perceived as gatekeepers that determine the implementation of the recommendations to break up prolonged sitting in the workplace [64], which was also identified in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that suggests the long-term indirect costs of employees’ presenteeism and absenteeism stemming from sedentary behaviour-associated illness might be higher than the cost of height-adjustable desks. For instance, height-adjustable desks cost ≥ £279 (US $375) per unit for a single display [61] and ≥ £305 (US $400) per unit for a dual display [62], which compares favourably with the indirect cost of presenteeism for businesses (which is far more than the cost of absenteeism) that was approximately £194 (US $255) per employee per annum [63]. Previous work has shown that organisational managers and employers are perceived as gatekeepers that determine the implementation of the recommendations to break up prolonged sitting in the workplace [64], which was also identified in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention aimed to reduce sitting and increase standing via feedback on sitting time, a range of tailored sitting-reduction techniques, and a desk-mounted SSW. Although originally designed to assess the acceptability of intervention components [21], our data transpired to predominantly offer insight into how office workers seek to reduce sitting and increase standing within the constraints of their working practices. While we also report intervention engagement, the main research question that guided the present analysis was: how did office workers experience their attempts to reduce sitting?…”
Section: Introductionmentioning
confidence: 99%
“…The study was registered (ISRCTN29395780). Deviations from our published protocol [21] are detailed in Additional file 1.…”
Section: Introductionmentioning
confidence: 99%
“…This may partly be because SB is a “non-conscious” behavior for which educational interventions alone are likely to have limited effects (A. H. Y. Chu et al, 2016; Gardner et al, 2017). According to expert consultation conducted by the National Health System, the United Kingdom, such multicomponent interventions should aim for at least 2 hours/day of standing and light activity (e.g., light walking) at work.…”
Section: Discussionmentioning
confidence: 99%